Implementasi Algoritma Levenshtein Distance Untuk Pencarian Judul Skripsi Dan Menambahkan Fitur Autocomplete Pada Website Repository Skripsi Jurusan Teknik Informatika Universitas Palangka Raya - Apriliansi, Elsa; Lestari, Ariesta; Sahay, Abertun Sagit (Journal of Information Technology and Computer Science, 2021)
Thesis is a scientific paper in the form of an exposition of research results. In saving a large number of theses, it takes a long time to search for thesis data one by one, so it requires a storage media that facilitates the speed in finding theses such as a repository. A website-based repository is one of the storage media that is needed to store the thesis data. In making their own repository website using the PHP programming language, MySQL database with a waterfall design model through the stages of analysis, design, programming, testing and maintenance. This website also adds the Levenshtein Distance algorithm to optimize searches so that search times become more efficient and adds an autocomplete feature that functions to provide word predictions or suggestions according to the characters typed by the user so as to help users search more for the words they want to search for. Based on the results of analysis and testing, the application of the Levenshtein Distance algorithm in finding the thesis title is able to display the thesis title which has the smallest or closest Distance value to the word inputted by the user. And for autocomplete itself, it is also able to display predictions or word suggestions that match the typed words and the calculation results for single target searches have an accuracy of 75% and multi-targets with 2 words have an accuracy of 50%. in accordance with the concept of the Levenshtein algorithm itself, the smaller the distance value obtained, the closer it is to the input thesis title.